MANAJEMEN KOMUNIKASI DALAM MENINGKATAN PELAYANAN INFORMASI PUBLIK - Herning Suryo S, Aditya Dwi Prasetyawan, Buddy Riyanto & (Transformasi, 2018)
Along with the development of technology and information, nowadays public information services provided by the Government are increasingly developing. One of the example is public complaint service facilities that is provided by the Department of communications and Informatics of Karanganyar Regency. Throughout its establishment, it already gets good response from the community which are marked by large number of complaint received. In contrary, the community feels like there is not much feedback given by the government or they just too slow to give a feedback. According to those phenomenon, the author is interested on finding the way to improve public communication service provided by Department of communication and Informatics Karanganyar Regency (Diskominfo Karanganyar) trough its management of public information service. The purpose of this study is to describe how communication management will improves the public information services in terms of dealing with community’s complaint. The type of research used in this study is descriptive with qualitative methods. As for the theory that is used such as the Cutlip, Center, and Broom's opinion which stated that the management of the operational communication includes defining the problem, planning, acting and communicating, as well as evaluating the communication activity. The results of this study explaines that communication management conducted by Diskominfo Karanganyar has been running quite well, which starts from defining the community’s problem through variety of complaint service and continued by classifying the incoming complaint before being forwarded to the associated govenment’s bureau. After that Diskominfo Karanganyar will select and filter the information that will be procedeed to the people, this activity is categorized as communication planning process. Karanganyar Diskominfo usually communicates directly to the public through a discussion forum as well as information technology media such as websites and social media. As for the evaluation conducted, Diskominfo usually coordinates a meeting every 3 months.Keywords: communication management, public information, Complaint commu